2009
DOI: 10.1111/j.1744-7402.2009.02418.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Optical Techniques for Noncontact Inspection of Y-TZP Parts

Abstract: A novel mid‐infrared transmission imaging (MIR‐TI) technique for the nondestructive, optical inspection of yttria‐stabilized tetragonal zirconia polycrystal (Y–TZP) components is described. This technique was designed specifically for the detection of flaws and cracks within the bulk of the ceramic component. The MIR‐TI technique exploits a transparency window in Y–TZP from 3 to 7 μm; at shorter wavelengths the material is highly scattering, while at longer wavelengths it is absorbing. We demonstrate that usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 53 publications
3
13
0
Order By: Relevance
“…This heating is thought not to have an adverse clinical effect because the porcelain is sintered on Y-TZP at higher than 1,000°C. Matysiak et al reported a similar result in which blackening occurred within holes on zirconia irradiated using a HeNe laser 16) . After heating at 1,350°C, the sample became white again, and there was no significant variation after the heat treatment.…”
Section: Darkening Of the Machined Y-tzp Surface And Corresponding Cosupporting
confidence: 55%
“…This heating is thought not to have an adverse clinical effect because the porcelain is sintered on Y-TZP at higher than 1,000°C. Matysiak et al reported a similar result in which blackening occurred within holes on zirconia irradiated using a HeNe laser 16) . After heating at 1,350°C, the sample became white again, and there was no significant variation after the heat treatment.…”
Section: Darkening Of the Machined Y-tzp Surface And Corresponding Cosupporting
confidence: 55%
“…The experimental setup of the CMIR-TI system is presented in Figure 2. The infrared camera used previously for the MIR-TI set-up [33] was replaced with a high detectivity Vigo PVI-2TE-8 infrared detector with a 300µm x 300µm active region. The infrared detector used in the experiments is a mesa structure Hg 1-x Cd x Te photodiode with a response time below 7 ns.…”
Section: The Confocal Mid-infrared Transmission Imaging (Cmir-ti) Tecmentioning
confidence: 99%
“…The chopper and the detector were connected to the lock-in amplifier (Scitec Instruments Model 420) to enhance signal stability and to reduce any external noise from various heat sources in the laboratory. A 50 µm pinhole (Thorlabs P50C) size was chosen to compare the results with the MIR-TI technique [33] which uses a 50 µm pixel size infrared camera sensor. Another motivation for the choice of a 50 µm pinhole was the limited amount of light reaching the infrared detector.…”
Section: The Confocal Mid-infrared Transmission Imaging (Cmir-ti) Tecmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were sectioned after the experiment with the thermocouples in place. To measure the radial distance between the hole and the thermocouple tip the cross‐sections were imaged with a thermal source and camera using a novel infra‐red imaging technique described in Matysiak et al 18 . The measured temperature data is shown in Fig.…”
Section: Femmentioning
confidence: 99%